2023
DOI: 10.5455/mjhs.2023.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice Regarding Insulin Use and its Adverse Effects in Adult Diabetic Population in a Tertiary Care Hospital

Abstract: Background and Aims: A proper assessment and understanding of knowledge, attitude and practice factors among patients is helpful in diabetes, for which prevention and control necessitate a lifelong adoption of healthy lifestyles. This study aims to assess the knowledge, attitude and practice regarding insulin use and its adverse effects among the diabetic population. Methods: A cross-sectional, observational, questionnaire-based study was conducted over a period of three months on patients of both type 1 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most of the patients and the pharmacists agreed that insulin therapy was more beneficial in regulating blood glucose levels in comparison with oral antidiabetic drugs; however, insulin injection was painful in 55.9% and 46.1% of the patients and pharmacists respectively. Most of them (60.4% of patients and 65.5% of pharmacists) did not agree with the fact that following the administration of insulin, a healthy diet was not needed to maintain blood glucose levels, same results were reported in a study conducted in Eastern India [ 34 ]. On the negative side, around half of the patients reported that they believe that regular use of insulin leads to addiction as they associate needles with drug abuse, and when they stop using insulin, they experience discomfort.…”
Section: Discussionmentioning
confidence: 79%
“…Most of the patients and the pharmacists agreed that insulin therapy was more beneficial in regulating blood glucose levels in comparison with oral antidiabetic drugs; however, insulin injection was painful in 55.9% and 46.1% of the patients and pharmacists respectively. Most of them (60.4% of patients and 65.5% of pharmacists) did not agree with the fact that following the administration of insulin, a healthy diet was not needed to maintain blood glucose levels, same results were reported in a study conducted in Eastern India [ 34 ]. On the negative side, around half of the patients reported that they believe that regular use of insulin leads to addiction as they associate needles with drug abuse, and when they stop using insulin, they experience discomfort.…”
Section: Discussionmentioning
confidence: 79%